2012
DOI: 10.1094/phyto-12-11-0343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature, Wetness Duration, and Planting Density on Olive Anthracnose Caused by Colletotrichum spp.

Abstract: The influence of temperature, wetness duration, and planting density on infection of olive fruit by Colletotrichum acutatum and C. simmondsii was examined in laboratory and field experiments. Detached olive fruit of 'Arbequina', 'Hojiblanca', and 'Picual' were inoculated with conidia of several isolates of the pathogen and kept at constant temperatures of 5 to 35°C in humid chambers. Similarly, potted plants and stem cuttings with fruit were inoculated and subjected to wetness periods of 0 to 48 h. Infection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 20 publications
1
38
0
3
Order By: Relevance
“…The microclimatic and agronomic conditions of SHD systems are highly conducive to airborne diseases. Thus, the differential resistance of the cultivars to major pests and diseases should also be taken into account when establishing an SHD orchard, especially in areas where Colletotrichum spp., the causal agent of olive anthracnose, is endemic (Moral et al, 2012). In addition, the numerous wounds in the branches caused by the mechanical harvester result in a greater risk of infections from wound-associated pathogens such as Botryosphaeriaceae species and the bacterium Pseudomonas savastanoi pv.…”
Section: Discussionmentioning
confidence: 99%
“…The microclimatic and agronomic conditions of SHD systems are highly conducive to airborne diseases. Thus, the differential resistance of the cultivars to major pests and diseases should also be taken into account when establishing an SHD orchard, especially in areas where Colletotrichum spp., the causal agent of olive anthracnose, is endemic (Moral et al, 2012). In addition, the numerous wounds in the branches caused by the mechanical harvester result in a greater risk of infections from wound-associated pathogens such as Botryosphaeriaceae species and the bacterium Pseudomonas savastanoi pv.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive field surveys in olivegrowing countries where epidemic outbreaks of olive anthracnose occur frequently have revealed that a different Colletotrichum species usually dominates in a particular area, thus suggesting an adaptive potential to different host genetic background and environmental factors Talhinhas et al, 2011). Optimum and cardinal temperatures and the ability to sporulate are among the factors that can influence the fitness of Colletorichum species and their adaptive capability to a particular environment Moral et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Environment is an integral component of disease development without the knowledge of which disease management is very difficult (Ghent et al, 2013). The characterization of favorable environmental conditions for disease development facilitates farmers and researchers for timely management of the disease (Moral et al, 2012). To eliminate unnecessary use of pesticides, precise knowledge of the risk of an epidemic at field level is essential (Dani, 2013).…”
Section: Introductionmentioning
confidence: 99%